THE INFLUENCE OF THINK PAIR SHARE STRATEGY TOWARDS STUDENTS’ SPEAKING ABILITY OF ENGLISH DEPARTMENT OF STKIP PGRI BANDAR LAMPUNG - Nurchurifiani, Eva (STKIP PGRI Bandar Lampung, 2019)
The problem of this research was many students got difficulties in speaking. In this research the researcher tried to investigate about think pair share in teaching speaking. The objective of this research were to know and describe the significant of the influence of think pair share strategy towards students’ speaking ability and to know and describe the average score of students’ speaking ability which is taught through think pair share is higher than which is taught through conventional technique. The research was conducted at second semester students of English Department of STKIP PGRI Bandar Lampung in 2017/2018. In this research the researcher used experimental method. The population ofthis research was94 students in 2 classes. The sample of the research were two classes, the first class was ENG IIB consisted of 47 students as the experimental class and the second class was ENG IIA consisted of 47 students as the control class. In the experimental class was the students were taught by think pair share strategy and in control class the students were taught by using the conventional technique. In conducting the research, the writer used Cluster Random Sampling technique to establish the experiment class and the control class, because all students were the sample is homogeneous. In data collecting technique, it was used spoken test, it is included instruction that students should make a composition based on the topic chosen. In data analysis, the writer used t-test formula. It was found that ttest > ttable = 2.98>1.67 for significant level 5% and ttable 2.39 for significant level 1%.It means thatHα is accepted. So, the researcher concluded that there is the influence of using think pair share strategy towards students’ speaking ability of English Department of STKIP PGRI Bandar Lampung in 2017/2018